2012
DOI: 10.1038/bjc.2012.458
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein C-II is prognostic for survival after pancreatic resection for adenocarcinoma

Abstract: Background:Pancreaticoduodenectomy remains a major undertaking. A preoperative blood test, which could confidently predict the benefits of surgery would improve the selection of pancreatic cancer patients for surgery. This study aimed to identify protein biomarkers prognostic for long-term survival and to validate them with clinico-pathological information.Methods:Serum from 40 preoperative patients was used to train for predictive biomarkers using surface-enhanced laser desorption/ionisation time-of-flight ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…Recent advances have shown that various proteomic values are proposed as prognostic factors for pancreatic adenocarcinoma; e.g., transthyretin [32], desmocollin 2 [33], Xb130 [34], heat shock protein 27 [35], extracellular high morbidity group box-1 [25], and apolipoprotein C-II [36]. In the current study, the seven-signal proteomic value showed unique characteristics compared with previously reported proteomics.…”
Section: Discussioncontrasting
confidence: 45%
“…Recent advances have shown that various proteomic values are proposed as prognostic factors for pancreatic adenocarcinoma; e.g., transthyretin [32], desmocollin 2 [33], Xb130 [34], heat shock protein 27 [35], extracellular high morbidity group box-1 [25], and apolipoprotein C-II [36]. In the current study, the seven-signal proteomic value showed unique characteristics compared with previously reported proteomics.…”
Section: Discussioncontrasting
confidence: 45%
“…47 Serum levels of APOC2 were elevated in pancreatic cancer patients compared to controls and had prognostic value for surgery. 48…”
Section: Apolipoprotein C and Cancermentioning
confidence: 99%
“…APOC2 acts as an important component of low‐density lipoproteins, very low‐density lipoproteins, and high‐density lipoproteins, where it assists to hydrolyze triglycerides associated with lipoproteins by activating lipoprotein lipase (LaRosa, Levy, Herbert, Lux, & Fredrickson, 1970). APOC2 has been demonstrated to be closely associated with survival of patients with pancreatic cancer (Xue et al, 2012). Elevated APOC2 promotes pancreatic cancer cell growth, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…APOC2 has been demonstrated to be closely associated with survival of patients with pancreatic cancer (Xue et al, 2012). Elevated APOC2 promotes pancreatic cancer cell growth, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%